" Being mutually involved in recovery". A hermeneutic exploration of nurses' experiences of patient participation in psychiatric care. Issue 1 (1st January 2021) - Wiklund Gustin, Lena
ABSTRACT: Purpose: This study aims at exploring how psychiatric nurses' experiences of patient participation could be understood from a caring science perspective. Methods: The design was inspired by clinical application research., which is a hermeneutic approach developed within caring science research. . In this study data were co-created during four reflective group dialogues where five participants' experiences of patient participation were reflected on in the light of caring science theory and research. The transcribed dialogues were subjected to a thematic, hermeneutic interpretation. Results: The interpretation gave rise to three themes; giving room for the patient to find his/her own pathway, strengthening personhood, and being in a balanced communion. From these themes an underlying pattern of the meaning of participation as being mutually involved in the patients' process of recovery arose. Conclusion: From a caring science perspective the meaning of psychiatric nurses experiences of patient participation could be understood as an interpersonal process reflecting the reciprocity in human relationships. This means a shift in understanding of patient participation from procedures related to the planning of nursing care, to understanding participation as a process focusing on the mutual involvement of patients and nurses in the patients' process of recovery.